Urogenital Tuberculosis: Urogenital TB - Kader, Md Abdul; Ansary, Eusha Ahmad Fidalillah; Md Arif, Nazim Uddin (Journal of the Medical College for Women & Hospital, 2025)
Mycobacterial seeding of the urogenital tract by hematogenous dissemination causes tuberculosis affecting the kidney and urologic system; this can happen after a lung infection, reactivation, or military disease. Kidney parenchymal lesions, such as glomerulonephritis and interstitial nephritis, are less frequent. Tuberculous bacteria have the ability to penetrate the medullary interstitium and result in development of granuloma. In the absence of obvious kidney disease, they may heal with accompanying fibrosis. Alternatively, years after the initial infection, they may burst and break down into the tubular lumen, releasing tuberculous bacilli into the urinary system and causing the infection to spread continuously. When an infection descends to the bladder and ureter, it results in hydronephrosis, ureteral stricture and blockage, and impaired kidney function. When individuals exhibit pertinent clinical symptoms and pertinent epidemiologic characteristics, urogenital tuberculosis should be suspected. Urinary frequency, hematuria, acidic urine, sterile pyuria, and/or dysuria are important clinical indicators for renal or urologic tuberculosis. Infertility, pelvic or abdominal discomfort, and/or menstrual abnormalities in women; nodular lesions of the scrotum, prostate, and/or testis in males; and nonhealing ulcers of the external genitalia in women are all signs of genital TB. Relatively seldom are systemic signs like fever and weight loss. The presence of tubercle bacilli in the urine can confirm the diagnosis of urogenital TB. Additionally, radiographic imaging is necessary for individuals who may have urologic or renal tuberculosis. When possible, contrast-enhanced computerized tomography is the preferable method; intravenous pyelography and high-resolution ultrasonography are other radiography methods. Antituberculous treatment is recommended for patients with urogenital TB; the main strategy is the same as for pulmonary TB. Surgical interventions are justified to a certain extent. J Med Coll Women Hosp.2025; 21 (2):166-174